Report of the Working Group on Agricultural Research and Education for the Seventh Five Year Plan (1985-90) - Planning Commission (Planning Commission, 1985)
Great strides have been made in agricultural production since sixties following massive application of science and technology, which helped in transforming Indian agriculture from a subsistence type into a commercial farming system. The impact of R&D efforts is reflected in the achievement of self-sufficiency in food grain production from 51 million tonnes in 1950-51 to a record production of about 150 million tonnes in 1983-84. Similar achievements have been made in potato, apple, cotton, tobacco, sugarcane, milk, poultry, fish production etc. The country now has one of the largest research &. training infrastructure to work on the production and other emerging problems confronting agriculture to meet growing demands for food, fodder and fibre.
Department of Agricultural Research and Education Ministry of Agriculture Government of India
Department of Agricultural Research and Education Ministry of Agriculture Government of India